White matter abnormalities in the Hdc knockout mouse, a model of tic and OCD pathophysiology - Jindachomthong, Kantiya; Yang, Chengran; Huang, Yuegao; Coman, Daniel; Rapanelli, Maximiliano; Hyder, Fahmeed; Dougherty, Joseph; Frick, Luciana; Pittenger, Christopher (Frontiers in Molecular Neuroscience, 2022)
Introduction An inactivating mutation in the histidine decarboxylase gene (Hdc) has been identified as a rare but high-penetrance genetic cause of Tourette syndrome (TS). TS is a neurodevelopmental syndrome characterized by recurrent motor and vocal tics; it is accompanied by structural and functional abnormalities in the cortico-basal ganglia circuitry. Hdc, which is expressed both in the posterior hypothalamus and peripherally, encodes an enzyme required for the biosynthesis of histamine. Hdc knockout mice (Hdc-KO) functionally recapitulate this mutation and exhibit behavioral and neurochemical abnormalities that parallel those seen in patients with TS. Materials and methods We performed exploratory RNA-seq to identify pathological alterations in several brain regions in Hdc-KO mice. Findings were corroborated with RNA and protein quantification, immunohistochemistry, and ex vivo brain imaging using MRI. Results Exploratory RNA-Seq analysis revealed, unexpectedly, that genes associated with oligodendrocytes and with myelin production are upregulated in the dorsal striatum of these mice. This was confirmed by qPCR, immunostaining, and immunoblotting. These results suggest an abnormality in myelination in the striatum. To test this in an intact mouse brain, we performed whole-brain ex vivo diffusion tensor imaging (DTI), which revealed reduced fractional anisotropy (FA) in the dorsal striatum. Discussion While the DTI literature in individuals with TS is sparse, these results are consistent with findings of disrupted descending cortical projections in patients with tics. The Hdc-KO model may represent a powerful system in which to examine the developmental mechanisms underlying this abnormality.